Exploring the impact of the political environment and national culture on readiness for internationalization in SMEs / Herwina Rosnan and Nuraisyah Chua Abdullah - Rosnan, Herwina; Chua Abdullah, Nuraisyah (Universiti Teknologi MARA Cawangan Selangor, 2018)
The purpose of this study is to examine the influence of the political environment and national culture on readiness for internationalization. The Smart-Partial Least Squares (PLS) analysis was used as to investigate the research model based on a survey of 60 Small and Medium-sized Enterprises (SMEs) from various industries which included companies in pharmaceutical, technological, electronic and foods and beverages industries in Klang Valley, Malaysia. The results supported the effects of two exogenous variables towards the endogenous variable Internationalization Readiness). Since the samples were limited to some SME companies in Klang Valley, Malaysia, the results of this study can only achieve theoretical generalization. Statistically, this study may prove not to be generalizable to the sample and should be confirmed using larger samples.